A numerical investigation of grease friction losses in labyrinth seals. (January 2020) - Augusto, L.L.X.; Sinatora, A.; Negrão, C.O.R.; Cousseau, T.
Abstract: A numerical study of the grease friction losses in three different configurations of axial and radial labyrinth seals under different rotational speeds was conducted. The results showed the grease rheology has a significant effect on the viscous torque. On the other hand, the number of labyrinth grooves does not affect substantially the torque for axial configuration but influences significantly the torque for radially oriented seals. Axially oriented seals have shown a better lubrication efficiency than radial labyrinths, especially when a non-Newtonian grease with small yield stress and index of consistency was used. The numerical model was also compared with a proposed analytical solution in which the differences were within an error band of 15%. Highlights: A numerical study of different lubricating greases inside axial and radial labyrinth seals was carried out. Axially oriented seals showed better lubrication efficiency when compared to radial configurations. The viscous torque dependence on the number of labyrinth grooves is negligible for axial but significant for radial seals. The viscous torque varies approximately with rotational speed to the power of n.